In Silico Study of Acmella uliginosa Leaf Compounds Interaction with Human Glucosidase - Marlina Kurnia, Nia (Journal Syifa Sciences and Clinical Research, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by hyperglycemia due to impaired insulin secretion or action. Glucokinase (GK) plays a crucial role in glucose homeostasis and is considered a promising therapeutic target for DM treatment. This study aims to evaluate the in silico interaction between the bioactive compound N-(2-phenylethyl)(2E,6Z,8E)-decatrienamide from Acmella uliginosa (Sw.) and the human GK crystal structure (PDB ID: 1V4S) using Molegro Virtual Docker software. Molecular docking analysis revealed that N-(2-phenylethyl)(2E,6Z,8E)-decatrienamide exhibits a high binding affinity to GK. Physicochemical and pharmacokinetic predictions using pkCSM indicate that this compound has a favorable pharmacokinetic profile, including high intestinal absorption and the ability to cross the blood-brain barrier. These findings suggest that N-(2-phenylethyl)(2E,6Z,8E)-decatrienamide is a promising candidate for the development of natural product-derived antidiabetic drugs. However, further in vitro and in vivo studies are required to validate its biological activity and safety.